Terapia fotodinâmica: estudo comparativa de luz led e laser sobre propionibacterium acnes in vitro - Ramos, Rogério Rodrigo (2018)
Propionibacterium acnes is a bacterium that causes acne. Photodynamic therapy is an alternative treatment for acne due to the side effects or the lack of response to treatment with oral or topical drugs. Photodynamic therapy is a consolidated therapeutic modality that produces its activity in the photooxidation of organic matter, which arises from the activity of reactive oxygen species. Objective: To evaluate the action of two types of 660nm red lights (Laser and LED) with the methylene blue photosensitizer on Propionibacterium acnes in vitro. Method: The experimental design was distributed into four groups (1 - control group without the application of light and without photosensitizer, 2 - application of light, 3 - Methylene Blue without light, and 4 - Methylene Blue with light). Tests were subjected to red (Laser - Light amplification by stimulated emission of radiation and LED - Light Emitting Diode) irradiation 660 nm by 4 cycles of 5 minutes at 3-minute intervals. Results: It was evidenced the prominence of the fourth cycle (20 minutes) of groups 2, 3 and 4 according to the Laser result. Despite the favorable results, the Laser irradiation time photosensitizer associated with Methylene Blue was not sufficient to inhibit bacteria’s proliferation completely. LED results showed that, there was a statistically significant reduction (p <0.05) in the means of group 4, although group 3 did not present statistical significance, but there was a reduction detected between the means. Conclusion: The photodynamic action is effective for the destruction of the biological material by irradiation at 660nm attributed to the process of photosensitization by the presence of the photosensitizer. Further studies in vitro are recommended to enable the clinical application of this photosensitizer in photodynamic therapy.